A tumor metastasis‐associated molecule TWIST1 is a favorable target for cancer immunotherapy due to its immunogenicity. Issue 8 (27th May 2022) - Yajima, Yuki; Kosaka, Akemi; Ishibashi, Kei; Yasuda, Shunsuke; Komatsuda, Hiroki; Nagato, Toshihiro; Oikawa, Kensuke; Kitada, Masahiro; Takekawa, Masanori; Kumai, Takumi; Ohara, Kenzo; Ohkuri, Takayuki; et al.
Abstract: Although neoantigens are one of the most favorable targets in cancer immunotherapy, it is less versatile and costly to apply neoantigen‐derived cancer vaccines to patients due to individual variation. It is, therefore, important to find highly immunogenic antigens between tumor‐specific or associated antigens that are shared among patients. Considering the cancer immunoediting theory, immunogenic tumor cells cannot survive in the early phase of tumor progression including two processes: elimination and equilibrium. We hypothesized that highly immunogenic molecules are allowed to be expressed in tumor cells after an immune suppressive tumor microenvironment was established, if these molecules contribute to tumor survival. In the current study, we focused on TWIST1 as a candidate for highly immunogenic antigens because it is upregulated in tumor cells under hypoxia and promotes tumor metastasis, which is observed in the late phase of tumor progression. We demonstrated that TWIST1 had an immunogenic peptide sequence TWIST1140–162, which effectively activated TWIST1‐specific CD4 + T‐cells. In a short‐term culture system, we detected more TWIST1‐specific responses in breast cancer patients compared with in healthy donors. Vaccination with the TWIST1 peptide also showed efficient expansion of TWIST1‐reactive HTLs in humanized mice. These findings indicate that TWIST1 is a highly immunogenic shared antigen and a favorable target for cancer immunotherapy. Abstract : We hypothesized that highly immunogenic molecules are allowed to be expressed in tumor cells after immune suppressive tumor microenvironment was established, if these molecules contribute to tumor survival.We found that a tumor metastasis‐associated molecule TWIST1 had an immunogenic enough to expand TWIST1‐specific T‐cells.These findings indicate that TWIST1 is a highly immunogenic shared antigen and a favorable target for cancer immunotherapy.